State-owned enterprises: Between subsidiarity and equal legal treatment - Galván Pareja, Gustavo (2017)
The Peruvian Constitution provides restrictions on the development of the stateowned enterprises and, in order to eliminate advantages and privileges, establishes equal legal treatment for state-owned and private companies. This article describes the constitutional regulation of state-owned enterprises and three cases in which the law provides a different legal treatment for private and state-owned companies.